Chronic Subthalamic Nucleus Stimulation in Parkinson's Disease: Optimal Frequency for Gait Depends on Stimulation Site and Axial Symptoms - Di Giulio, Irene; Kalliolia, Eirini; Georgiev, Dejan; Peters, Amy L.; Voyce, Daniel C.; Akram, Harith; Foltynie, Thomas; Limousin, Patricia; Day, Brian L. (Frontiers in Neurology, 2019)
Axial symptoms emerge in a significant proportion of patients with Parkinson's disease (PD) within 5 years of deep brain stimulation (STN-DBS). Lowering the stimulation frequency may reduce these symptoms. The objectives of the current study were to establish the relationship between gait performance and STN-DBS frequency in chronically stimulated patients with PD, and to identify factors underlying variability in this relationship. Twenty-four patients treated chronically with STN-DBS (>4 years) were studied off-medication. The effect of stimulation frequency (40–140 Hz, 20 Hz-steps, constant energy) on gait was assessed in 6 sessions spread over 1 day. Half of the trials/session involved walking through a narrow doorway. The influence of stimulation voltage was investigated separately in 10 patients. Gait was measured using 3D motion capture and axial symptoms severity was assessed clinically. A novel statistical method established the optimal frequency(ies) for each patient by operating on frequency-tuning curves for multiple gait parameters. Narrowly-tuned optimal frequencies (20 Hz bandwidth) were found in 79% of patients. Frequency change produced a larger effect on gait performance than voltage change. Optimal frequency varied between patients (between 60 and 140 Hz). Contact site in the right STN and severity of axial symptoms were independent predictors of optimal frequency (P = 0.009), with lower frequencies associated with more dorsal contacts and worse axial symptoms. We conclude that gait performance is sensitive to small changes in STN-DBS frequency. The optimal frequency varies considerably between patients and is associated with electrode contact site and severity of axial symptoms. Between-subject variability of optimal frequency may stem from variable pathology outside the basal ganglia.